REFLECTION AND BIOGRAPHIC MADIATION IN MATHEMATICS TEACHERS POSTGRADUAL TRAINING PROCESSES - Salazar Amaya, Claudia (2024)
Reporting the results of the evaluation phase of a design experience, development, and curricular evaluation within the framework of an advanced training program for mathematics teachers. This experience takes place during the Master on Mathematics Teaching at the National Pedagogical University in Bogotá-Colombia. In this experience, reflection on issues of the identity of the mathematics teacher is assumed as an articulator of the training trajectory and biographical mediation in postgraduate training processes as a trigger for reflective thinking. Based on experience, program teachers confirm that reflective thinking on the ground takes pedagogical practice in class as an object, as well as other spheres of the dimension of doing, as well as the dimensions of being and knowledge and the interactions between these three dimensions, which are intertwined to give way to the teacher's professional identity. Therefore, we recognize that the stage of the postgraduate program causes profound transformations in the identity of teachers, which allows the refiguration of mathematics teachers.